Optimizing the Synthesis of Lignin Derivatives from Acacia mangium to Improve the Enzymatic Hydrolysis of Kraft Pulp Sorghum Bagasse - Widya Fatriasari; Fajar Nur Hamzah; Bagas Ikhasan Pratomo; Triyani Fajriutami; Riksfardini Annisa Ermawar; Faizatul Falah; Raden Permana Budi Laksana; Muhammad Ghozali; Apri Heri Iswanto; Euis Hermiati; Ina Winarni (International Journal of Renewable Energy Development, 2020)
The present study is aimed at optimizing the synthesis of Amphipilic lignin derivatives (A-LD) from the isolated lignin of A.mangium black liquor (BL), using the one and two step acid isolation method, and commercial lignin (LS) was used as comparison. The experimental design was conducted using Taguchi method, which consisted of four parameters and two level factors, with reference to the matrix orthogonal array, L8, including temperature, reaction time, amount of polyethylene glycol diglycidylethers (PEGDE) and Kraft lignin (KL). Furthermore, the kraft pulp of sweet sorghum bagasse (SSB) was used as substrate in the enzymatic hydrolysis (NREL method), with addition of A-LD, whose functional group and surface tension were then characterised using ATR-FTIR and surface tension equipment. Conversely, an improvement in the reducing sugar yield (RSY) compared to the control was observed after adding various A-LDs to the substrate during enzymatic hydrolysis. This product was more prospective for L2S than others products under milder circumstances, due to the fact that it possesses the lowest surface tension. Also, Taguchi analysis demonstrated the treatment at 60 °C for 1 h with 3.0 g and 1.0 g of PEDGE and lignin, respectively as the optimum condition, while the amount of lignin present was included as a factor with the propensity to significantly affect A-LD L1S and LS. Therefore, it was established that the A-LDs from A. mangium kraft lignin require milder synthesis conditions, compared to other existing methods and despite the differences in optimum experimental condition for L2S and LS, the functional groups in the IR spectra possessed very identical characteristics.